Strategic management - Rothaermel, Frank T
Revised edition of the work, Strategic management : concepts; Includes bibliographical references and indexes; What is strategy, and why is it important? -- Strategic leadership : managing the strategy process -- External analysis : industry structure, competitive forces, and strategic groups -- Internal analysis : resources, capabilities, and core competencies -- Competitive advantage, firm performance, and business models -- Business strategy : differentiation, cost leadership, and integration -- Business strategy : innovation and entrepreneurship -- Corporate strategy : vertical integration and diversification -- Corporate strategy : mergers and acquisitions, strategic alliances -- Global strategy : competing around the world -- Organizational design : structure, culture, and control -- Corporate governance and business ethics